Development and psychometric properties of the Knowledge and Attitudes to Mental Health Scales (KAMHS): a psychometric measure of mental health literacy in children and adolescents - Nicola J. Simkiss; Nicola S. Gray; Chris Dunne; Robert J. Snowden (BMC, 2021)
Abstract Background Adolescence is a crucial period for the acquisition of good mental health behaviours, which are the foundation for health and wellbeing in later life. Improved knowledge about mental health and improved help-seeking behaviours have been shown to lead to better mental health outcomes. Mental health literacy (MHL) is multifaceted (e.g., knowledge about symptoms, the stigma around mental health, good mental health practices, etc.). Measures are needed that can assess these different aspects of MHL. Measurement of mental health literacy is currently limited due to a lack of reported psychometric instruments with known psychometric properties. Given that most mental health problems start in early adolescence, a scale is needed that is reliable and valid in this age group. Methods The development and validation of the psychometric instrument (termed the Knowledge and Attitudes to Mental Health Scales: KAMHS) entailed two phases: 1) item generation based on an evidence-based intervention programme: The Guide; and 2) item reduction through exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) for factor structure and psychometric assessment. Participants were 559 Year 9 pupils in secondary schools across Wales aged between 13 and 14 years. Results Results from the CFA indicated an acceptable fit of the model to the data. The KAMHS showed good internal constancy and moderate test-retest validity (.40-.64). Conclusions The final version of the KAMHS contains 50 items that are appropriate for use in children and adolescents. These results suggest that the KAMHS can be used over time to assess the efficacy of interventions aimed at increasing the mental health literacy of adolescent populations.